Sistem Pendukung Keputusan Menentukan Mekanik Terbaik Menggunakan Metode Simple Additive Weighting - Mahadika Bayu Pradipta; Tutus Praningki (STT Cahaya Surya Kediri, 2018)
Ahass Aries Sentosa Motor Kediri is one of the leading motorcycle dealers and workshops in Kediri. One of the key factors in getting a well-known predicate from consumers is the mechanical quality factor, especially in motorcycle service in the workshop Ahass Aries Sentosa Motor Kediri. The use of a decision support system is very helpful in determining the best mechanics, and is accompanied by the method of Simple Additive Weighting (SAW), this method can complete the research by looking for weight values for each attribute, then ranking process that will determine the optimal alternative, namely the entitled mechanics got the title as the best mechanic. With the decision support system with Simple Additive Weighting (SAW) method applied to this problem because it is able to select the best alternative from a number of alternatives. In this case it will be easier to monitor, select and determine the mechanics who are entitled to the title as the best mechanic.